Origin of light instability in amorphous IGZO thin-film transistors and its suppression - Mallory Mativenga (Nature Portfolio, 2021)
Abstract Radiating amorphous In–Ga–Zn–O (a-IGZO) thin-film transistors (TFTs) with deep ultraviolet light (λ = 175 nm) is found to induce rigid negative threshold-voltage shift, as well as a subthreshold hump and an increase in subthreshold-voltage slope. These changes are attributed to the photo creation and ionization of oxygen vacancy states (VO), which are confined mainly to the top surface of the a-IGZO film (backchannel). Photoionization of these states generates free electrons and the transition from the neutral to the ionized VO is accompanied by lattice relaxation, which raises the energy of the ionized VO. This and the possibility of atomic exchange with weakly bonded hydrogen leads to metastability of the ionized VO, consistent with the rigid threshold-voltage shift and increase in subthreshold-voltage slope. The hump is thus a manifestation of the highly conductive backchannel and its formation can be suppressed by reduction of the a-IGZO film thickness or application of a back bias after radiation. These results support photo creation and ionization of VO as the main cause of light instability in a-IGZO TFTs and provide some insights on how to minimize the effect.